Changing of the school-leaving exam in information technology - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2003)
This paper deals with the main problem of the school-leaving exam in information technology – design and contents of exam for 2004. The first school-leaving exam in informatics was organized in 1994/1995. Since the 1999/2000 school year, a profiled model was implemented on all the secondary education levels. Following that two types of the exam in information technology are proposed. The first one – information technology – is intended for students whose learning aim is to acquire skills for using computers in every day life. The second one – information technology (programming) – for those who want to be advanced users and programmers. The main attention is paid to the aims, structure, and contents of exam.